Exploring the Nursing Factors Related to Ventilator-Associated Pneumonia in the Intensive Care Unit - Yin, Yanling; Sun, Meirong; Li, Zhe; Bu, Jingjing; Chen, Yuhong; Zhang, Kun; Hu, Zhenjie (Frontiers in Public Health, 2022)
Objectives:To explore nursing risk factors associated with ventilator-associated pneumonia(VAP). Committing to provide the basis for future nursing training and quality control for technical offices. Methods:Through the quality control platform of Hebei province, questionnaires were sent to the intensive care nurses in 37 tertiary hospitals(5 hospitals were excluded due to incomplete information) in Hebei province, China, to collect the incidence of VAP and the nursing status of them. All date was analyzed using an independent t-test, ANOVA, and Pearson correlation. Resluts:Two central themes were derived from the data analysis:Nurse human resources and standard of nursing practice.The incidence of VAP was higher when the proportion of nurses working less than five years and the number of nurses working night shifts increased. The incidence of VAP was lower when the sputum suction tube radius was smaller and the selected oral care solution had disinfection effect. Conclusions:The incidence of VAP is closely related to nursing factors.Choose different thickness of sputum suction tube and oral nursing liquid will lead to different outcomes.In addition, different nursing staff structure and scheduling mode will directly affect the incidence of VAP. Therefore, we should continue to standardize and unify nursing operation, and optimize nursing staff structure and scheduling mode.